Personalization of freestyle wrestlers` training process by influence the anaerobic systems of energy supply - Sybil, M. G.; Pervachuk, R. V.; Trach, V. M. (Journal of Physical Education and Sport, 2015)
The paper contains results of the experiment with the individualization of training process of skilled freestyle wrestlers by influencing individual components of the mechanism of anaerobic energy supply. Statistically significant improvement of special performance of the main group of all cluster presentatives: non-lactate, lactate and mixed has been established.